Mindfulness Practices to Improve Achievement - Natalia, Karina; Utomo, Budi; Suherman, Heru (Journal of Education Technology Information Social Sciences and Health, 2024)
McClelland Wanless (2012) emphasize individuals' abilities to consciously regulate their thoughts, emotions, and behaviors, involving emotional and behavioral aspects. This research employs a literature study approach to delve into existing literature and summarize knowledge. A profound understanding of the interaction between procrastination, mindfulness, and self-regulation can provide a foundation for effective intervention strategies in higher education settings. The focus on developing self-regulation skills and enhancing mindfulness can be key steps in assisting students in overcoming procrastination and achieving optimal academic performance